Politicizing climate change in times of populism: an introduction. Issue 5 (29th July 2022) - Marquardt, Jens; Lederer, Markus
ABSTRACT: With this introduction to the special issue on climate politics, democracy, and populism, we lay the ground for the multiplicity of analyses that follow. We highlight the essentially contested nature of concepts like (de-)politicization, populism, and democracy that reject the notion of a single definition. We do so by outlining what post-, de-, and re-politicization can mean, how diverse the perspectives on populism are, and which ones help guide us in this special issue. We present the different arenas where the politicization of climate change is happening and which mechanisms are at work, particularly concerning right-wing populism. We discuss our joint understandings of democratic governance and what challenges, as well as opportunities, populism brings to the table. We do not provide a single theoretical framework but rather a typology of the various understandings of these concepts to outline how each contribution relates to it.